2018
DOI: 10.1155/2018/6378643
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and Hardened Properties of Self‐Leveling Mortars with Porcelain and Red Ceramic Wastes

Abstract: Self-leveling mortar (SLM) has several advantages when compared to the conventional mortar used in subfloors, especially when productivity is desired. In Brazil, the use of SLM is not still widespread related to conventional mortar. Few builders are using it in constructions. In the same way, the sustainable reuse of wastes in building materials is not so great, but it has grown, becoming increasingly important. In Brazil, a great amount of waste is generated by the manufacture of electrical porcelain insulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…For ceramics, similar results were found in the studies by Pereira and Camarini [4], who indicated that the 50% replacement of Portland cement with red ceramic did not significantly influence the cement hydration process, therefore, using the heat of hydration as an evaluation parameter can be a viable alternative.…”
Section: Heat Of Hydrationsupporting
confidence: 82%
See 4 more Smart Citations
“…For ceramics, similar results were found in the studies by Pereira and Camarini [4], who indicated that the 50% replacement of Portland cement with red ceramic did not significantly influence the cement hydration process, therefore, using the heat of hydration as an evaluation parameter can be a viable alternative.…”
Section: Heat Of Hydrationsupporting
confidence: 82%
“…However, like other cementitious materials, they require large amounts of cement, as they have an inverse relationship between workability and mechanical strength [3], making it difficult to obtain fluid mixtures with absence of exudation and/or segregation [4]. Aiming to modify the rheological properties of mixtures, chemical additives are used, raising the cost of these materials [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations